Validity of Immunochromatographic Test for Antibody in Diagnosis of Typhoid Fever in Children Admitted in A Tertiary Care Hospital - Choudhury, Zabeen; Karim, Mohammed Rezaul; Samad, Rasheda; Islam, Shanjana (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2018)
Background: To determine the Validity of Immunochromatographic Test (ICT) in diagnosis of typhoid fever in children admitted in a tertiary care hospital. Methods: This cross sectional study was carried out the in Pediatric & Medicine wards of Chittagong Medical College Hospital (CMCH), Chittagong during the period July 2012 to June 2013. A total number of 150 clinically suspected cases of typhoid fever (Age >6 months to18 years) were enrolled in this study. After taking informed written consent, detailed history & clinical examination were completed. A blood culture sample was taken on the day of admission before starting antibiotic. On the 5th day onwards of appearance of fever, blood sample was taken to perform ICT. Patients received standard medical treatment of the admitting wards. Results: Blood C/S for Salmonella typhi was found positive in 16(10.7%) cases. Positive ICT for typhoid fever was found in 37(24.7%) cases. Among then, IgM was 18(12.0%) IgM+IgG were 8(5.3%) and IgG was 11(7.3%). ICT found true positive in 14, false positive in 23, false negative in 2 and true negative in 111 cases, where blood culture considered as gold standard. The difference was statistically significant (p<0.05) between two groups. Immunochromatographic Test (ICT) showed sensitivity 87.5%, specificity 82.8%, accuracy 83.3%, positive predictive value 37.8% and negative predictive value 98.2% for identification of typhoid fever. Conclusion: The present study has shown high sensitivity & specificity of ICT, it can be used as a useful & prospectful diagnostic tool. Chatt Maa Shi Hosp Med Coll J; Vol.16 (2); July 2017; Page 20-24